(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the correlation between depression, psychological well-being, and attitudes toward psychological help seeking in surgical patients.Material and Methods: This was a correlative descriptive study conducted. In the study, the whole of the population was tried to be reached without using sample selection and the study was completed with 333 patients hospitalized in surgical clinics between October 2018 and February 2019. The Beck Depression Inventory (BDI), Attitudes towards Seeking Psychological Help Scale-Shortened (ASPH-S) and the Psychological Well-being Scale (PWBS) were used for the data collection. Mann-Whitney U test was used for the comparison of two variables, and Kruskal-Wallis test was used for the comparison of more than two variables. Cronbach’s Alpha reliability analysis test were used to assess the data. Spearman’s correlation test was used to analyze the relationship between BDI, ASPH-S and PWBS.Results: It was found that patient’s age, gender, educational status, marital status, number of children, family structure, having a chronic disease, being applied to a psychiatrist in the last year and using a psychiatric drug had a statistically significant effect on BDI scores (p .05). Patient’s educational status, socioeconomic status and having a chronic disease had a statistically significant effect on PWBS scores (p .05). Patient’s socioeconomic status, where they came from, being applied to a psychiatrist in the last year and using a psychiatric drug had a statistically significant effect on ASPH-S scores (p .05). There was also a negative and weak relationship between BDI and PWBS (r=0.298, p .05) and ASPH-S (r = 0.209, p .05) and a positive and moderate relationship between PWBS and ASPH-S (r=0.317, p .05).Conclusions: Patient’s sociodemographic characteristics affected the BDI, PWBS and ASPH-S scores of the patients with surgical problems. The nurses should determine the positive and negative predictors of attitudes toward seeking professional psychological help in patients hospitalized in surgical clinics.Keywords: Surgical Patients; Depression; Psychological Well-Being; Seeking Psychological Help.